A material turn in International Relations: the 4x4, intervention and resistance. Issue 5 (7th June 2017) - Mac Ginty, Roger
Abstract: This article explores how analysis of material objects offers insights into international intervention and reactions to that intervention. Building on studies that examine the 4x4 as emblematic of intervention, the article argues that the 4x4 can also be seen as an object of resistance and agency. To do so, it uses the case study of 4x4 usage in Darfur and draws on primary data including interviews and a UN security incident database. The article is mindful of the limitations of a 'material turn' in the study of International Relations, especially in relation to how it might encourage us to overlook agency and structural power. While finding new materialism arguments largely convincing, the case study encourages a note of caution and proposes the notion of 'materialism+', which allows for the further investigation of the human/non-human interface, but is circumspect about tendencies towards neophilia, dematerialism, and posthumanism.